Analyzing the Relationship Between Critical Thinking, Learning Outcomes, and Retention Using Jigsaw Learning Model - Aini, Intan Nur; Siswati, Bea Hana; Fiarani, Hajar Syifa (FKIP Universitas Lampung, 2025)
Abstract: Critical thinking skills are one of the key skills needed to face the challenges of the 21st century. However, based on the 2015 PISA study, students' critical thinking skills in Indonesia are still low. Various studies have shown a significant contribution of critical thinking skills to learning outcomes. In addition, the development of critical thinking skills in biology learning can improve student retention. However, not many studies have specifically examined the relationship of critical thinking skills with learning outcomes and student retention, especially with the use of the Jigsaw cooperative learning model. This study aims to examine the relationship of critical thinking skills with student learning outcomes and retention through the Jigsaw learning model. This correlational study involved 72 students in grades X5 and X6 at SMA Negeri 4 Jember. The results of product moment correlation analysis showed a significant relationship between critical thinking skills with learning outcomes (R = 0.967, R² = 93.5%, significance < 0.001) and student learning retention (R = 0.511, R² = 26.1%, significance < 0.001). Thus, critical thinking skills contributed 93.5% to learning outcomes, while 6.5% was influenced by other factors. Meanwhile, on student retention, the contribution of critical thinking skills was 26.1%, with 73.9% influenced by other factors. Keywords: critical thinking skills, learning outcomes, retention, Jigsaw learning model.